2022
DOI: 10.1177/08862605221124253
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and Gender Minority Victimization: Base Rates of Assault in College Students Across Sexual and Gender Identities

Abstract: Past findings have indicated that sexual and gender minority (SGM) individuals experience disproportionate rates of emotional, physical, and sexual assault compared to their heterosexual/cisgender counterparts. While these findings are robust, many studies report homogenous groupings of SGM participants. This practice likely masks important between-group differences. We sought to address this issue by examining reported base rates of emotional, physical, and sexual assault within 12 months of data collection, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…It is possible that some nonmonosexual groups might experience more minority/nonmonosexual stress than others (Meyer, 2003). For example, a recent study found that pansexual students had higher rates of assault than other SD subgroups whereas asexual students had lower rates than other SD subgroups (Borgogna et al, 2023). It is also possible that asexual identifying students might not experience many nonmonosexual specific stressors documented among other nonmonosexual groups (e.g., bisexual) such as hypersexualization and stereotypes regarding promiscuity (Dyar et al, 2020; Feinstein & Dyar, 2017), although asexual students might certainly experience other unique subgroup stressors.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that some nonmonosexual groups might experience more minority/nonmonosexual stress than others (Meyer, 2003). For example, a recent study found that pansexual students had higher rates of assault than other SD subgroups whereas asexual students had lower rates than other SD subgroups (Borgogna et al, 2023). It is also possible that asexual identifying students might not experience many nonmonosexual specific stressors documented among other nonmonosexual groups (e.g., bisexual) such as hypersexualization and stereotypes regarding promiscuity (Dyar et al, 2020; Feinstein & Dyar, 2017), although asexual students might certainly experience other unique subgroup stressors.…”
Section: Discussionmentioning
confidence: 99%